Age-Specific Sex Differences in Magnetic Resonance Imaging-Depicted Carotid Intraplaque Hemorrhage. Issue 8 (August 2017) - Singh, Navneet; Moody, Alan R.; Zhang, Bowen; Kaminski, Isabella; Kapur, Kush; Chiu, Stephanie; Tyrrell, Pascal N.
Abstract : Background and Purpose—: Stroke rates are higher in men compared with women in the fourth through seventh decades of life, and higher rates may result from differences in carotid intraplaque hemorrhage (IPH), an unstable atherosclerotic plaque component. We report age-specific sex differences in the presence of magnetic resonance imaging-depicted carotid IPH. Methods—: Patients (n=1115) underwent magnetic resonance imaging for carotid IPH between 2005 and 2014. Low-grade carotid stenosis patients (n=906) without prior endarterectomy were eligible for this cross-sectional study. Results—: Of the 906 patients included (mean age±SD in years, 66.98±15.15), 63 (6.95%) had carotid IPH. In men and women, carotid IPH was present in 11.43% (48 of 420) and 3.09% (15 of 486), respectively ( P <0.0001). Multivariable logistic regression analysis confirmed greater odds of carotid IPH in men for all ages: 45 to 54 (odds ratio=45.45; 95% confidence interval, 3.43–500), 55 to 64 years (odds ratio=21.74; 95% confidence interval, 3.21–142.86), 65 to 74 years (odds ratio=10.42; 95% confidence interval, 2.91–37.04), and ≥75 years (odds ratio=5.00; 95% confidence interval, 2.31–10.75). Male sex modified the effect of age on the presence of carotid IPH (β=0.074; SE=0.036; P =0.0411). Conclusions—: Men have greater age-specific odds of magnetic resonance imaging-depicted carotid IPH compared with women. With increasing age post-menopause, the odds of carotid IPH in women becomes closer to that of men. Delayed onset of carotid IPH in women, an unstable plaque component, may partly explain differential stroke rates between sexes, and further studies are warranted.